Prevalence of body weight dissatisfaction among adolescents: a systematic review - Mariana Contiero San Martini; Daniela de Assumpção; Marilisa Berti de Azevedo Barros; Josiemer Mattei; Antônio de Azevedo Barros Filho (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: To identify the prevalence of weight dissatisfaction among adolescents aged 10-19 years and stratify the analysis by sex. Data source: A literature review of cross-sectional studies among healthy adolescents was performed. The U.S. National Library of Medicine/National Institutes of Health (PubMed), Ovid® (Wolters Kluwer), The Cumulative Index to Nursing and Allied Health Literature (CINAHL), and American Psychological Association (PsycINFO®) databases were searched between May 2019 and January 2020. Data synthesis: Initially, 3,700 records were identified, and 10 papers were obtained through other sources. After the removal of duplicates, 1,732 records were screened based on the titles and abstracts, and 126 were preselected for full-text analysis. After the application of the eligibility criteria, 34 papers were included in the present review. The studies were published between 1997 and 2020. The sample size ranged from <150 to >103,000 adolescents. The prevalence of weight dissatisfaction ranged from 18.0 to 56.6% in both sexes (10.8-82.5% among boys and 19.2-83.8% among girls). Conclusions: Based on the findings of the present systematic review, the prevalence of weight dissatisfaction is high among adolescents, especially girls. Such information can contribute to the planning of health and education programs addressing the issue of weight in adolescents.